Nanoencapsulation of individual mammalian cells with cytoprotective polymer shell. (July 2017) - Yang, Jianmin; Li, Jingchao; Li, Xiaomeng; Wang, Xinlong; Yang, Yingjun; Kawazoe, Naoki; Chen, Guoping
Abstract: Nanoencapsulation of individual mammalian cells has great potential in biomedical, biotechnological and bioelectronic applications. However, existing techniques for cell nanoencapsulation generally yield short sustaining period and loose structure of encapsulation shell, which fails to meet the long-term cytoprotection and immunosuppression requirements. Here, we report a mild method to realize the nanoencapsulation of individual mammalian cells by layer-by-layer (LbL) assembly of gelatin inner layer and cross-linking of poly(ethylene glycol) (PEG) outer layer through thiol-click chemistry. With the present method, the encapsulated individual HeLa cells showed a high viability, long persistence period and effective resistance against macro external entities and high physical stress. Moreover, on-demand cell release could also be achieved by selective cleavage of succinimide thioether linkage in the outer PEG layer. The approach presented here may provide a new and versatile method for the cleavable nanoencapsulation of individual mammalian cells. Graphical abstract: